Generalized Gaussian Numbers Related to Linear Codes over Galois Rings - Salturk, Esengul; Siap, Irfan (EUROPEAN JOURNAL PURE & APPLIED MATHEMATICS, 2012)
In this paper, we define a family of Generalized Gaussian Numbers that gives the number of linear codes over Galois rings directly. Also, we study some of their properties and obtain some relations between them.
Keywords: Gaussian binomial coefficients; linear codes over rings; Mathematics